Enhanced combined assimilative and bound phosphorus uptake in concurrence with nitrate removal in pre-anoxic cyclic sequencing batch reactor - Khursheed, Anwar; Ali, Muntjeer; Munshi, Faris Mohammad A.; Alali, Abdulrhman Fahmi; Kamal, Mohab Amin; Almohana, Abdulaziz Ibrahim; Alrehaili, Omar; Gaur, Rubia Z.; Tyagi, Vinay Kumar; Khan, Abid Ali; Goel, Gaurav (Elsevier, 2022)
Needless to specify, controlling nitrogen and phosphorus discharge from wastewater treatment plants is synonymous with the prevention of eutrophication of surface waters, as one of the major issues related to water security. The present study investigates the performance of a pre-anoxic sequencing batch reactor (SBR) working on the basis of intermittent aeration, operated at varied carbon (bCOD) to nitrogen (C/N) ratio of 3, 7.5, and 10, and readily biodegradable (rbCOD) to slowly biodegradable (sbCOD) ratio of 0.1, 0.25, and 0.5. The findings revealed that an enhanced nitrogen removal was observed, together with higher C/N and rbCOD to sbCOD ratios. The results also show a consistent increase in total phosphorus removal with an increase in nitrogen removal. The phosphorus uptake of sludge varied from 0.02 – 0.045 mgP/mgVSS (avg. 0.031 ± 0.004), which resulted in enrichment levels of 0.88 – 1.68 times the stoichiometric value of 0.0267 mgP/mgVSS (avg. 1.45 ± 0.14). On an average basis, the assimilative total phosphate (TP) content was increased by 0.008 gTP/gNO -/3 -N removal rate. The excess phosphorus removal was due to the formation of poorly soluble polyvalent phosphate compounds, which was found based on dry analysis, which persisted as bound phosphate in the sludge.
Keywords: Enhanced phosphate uptake; Carbon to nitrogen ratio; rbCOD; sbCOD; SBR